Intraocular Lens Power Calculation among Patients with a History of Keratorefractive Surgery: Comparison of Historical and Non-Historical Methods: Comparison of Historical and Non-Historical Methods - Moradi, Ali; Aghazadeh-Amiri, Mohammad; Shojaei, Ahmad; Mohammad Rabei , Hossein; Tabatabaeem , Mehdi; Noorizadeh, Farsad; Pirasteh , Zahra (Journal of Ophthalmic and Optometric Sciences, 2023)
Purpose: To compare the accuracy of historical and non-historical methods in intraocular lens (IOL) power calculation among patients undergoing cataract surgery with a history of keratorefractive surgery. Patients and Methods: In this cross-sectional study, patients undergoing cataract surgery were divided into two groups: the first group consisted of patients with available previous data regarding their history of keratorefractive surgery, and the second group included patients without any previous data. Corneal power was corrected using the clinical history method (CHM) in the first group and the Shammas no history method (SNHM) in the second group. IOL power for both groups was calculated using the Holladay I formula for implanting an SA60AT or SN60WF lenses. The main outcome measure was the mean refractive error three months after cataract surgery. Results: One hundred twenty-nine eyes from 104 cataract patients with a history of myopic keratorefractive surgery were included in this study. The IOL calculation in 64 eyes was performed using the CHM method, and in 65 eyes using the SNHM method. The mean refractive error after cataract surgery was -0.17 ± 1.09 D in the CHM group and -0.09 ± 0.75 D in the SNHM group, indicating no statistically significant difference between the two methods (P = 0.62). Conclusions: The SNHM showed no significant difference compared to the CHM in terms of post-surgical mean refractive error. Given the ease of performing the SNHM and the similarity in post-surgical refractive outcomes, it suggests that the SNHM can serve as an alternative to the CHM.